THE DYNAMICS OF INNOVATION DEVELOPMENT FOR ENTERPRISES OF THE REPUBLIC OF TATARSTAN IN THE CONDITIONS OF SUPPLY CHAIN MANAGEMENT AND DIGITAL ECONOMY - Arkadevna Kodolova, Irina; Mirgaziyanovna Yusupova, Lilia; Viktorovna Nikonova, Tatyana; Irekovna Agliullina, Zarina (International Journal of Supply Chain Management, 2019)
Abstract- The strategic aim of the Russian economic progress is about transition to innovative development model by considering the digital economy and supply chain management. The main tasks of country government in program decisions are: organization of national innovative system and creating its infrastructure which provides technological modernization of economics, increasing of competitiveness based on hi-tech, transforming scientific potential into one of the main sources of sustained economic growth. The article presents an analysis of innovative activity dynamics in enterprises of the Republic of Tatarstan. The innovative activity of enterprises in the Republic was analyzed, indicators of shipped innovative products were viewed. The characteristics were given according to main indicators of transfer and commercialization of innovative technologies. The results of innovative activity in enterprises at the regional level were summarized.